Correlation analysis between sleep quality and the mental health status of female sex workers during the COVID-19 pandemic in Hubei Province - Zhai, Piyong; Liu, Hao; Zhang, Yutong; Huang, Tao; Xiong, Change; Liu, Yang; Wang, Guiping; Chen, Xin; Tan, Jianhua; Jiao, Chengjun; Zhan, Jianbo; Cheng, Jing (Frontiers in Endocrinology, 2023)
Objective Female sex workers (FSWs) in entertainment venues are subject to condemnation and rejection by their families and the outside world. As a result, they are prone to psychological problems, including anxiety and even suicidal tendencies. The aim of the current study was to understand the sleep and mental health status of local FSWs and to identify associated risk factors, so as to provide a scientific basis for improving the social recognition of FSWs and establishing effective psychological interventions. Methods A stratified cluster random sampling method was used to select women engaged in commercial sex in bathing, sauna, karaoke halls and other entertainment venues. A self-designed questionnaire assessing mental health-related factors was administered face-to-face with the respondents. 90 participants were randomly selected for blood tests to analyze the relationship between biological indicators and sleep quality. Results The rates of depression, anxiety and somnipathy among FSWs were 32.7%, 43.1% and 8.6%, respectively. The correlation coefficients (r) between sleep quality and depression, anxiety and social support were 0.07, 0.09 and -0.09, respectively. Divorce or widowhood, technical secondary school education, alcohol consumption and exercise were independent risk factors for depression in FSWs (p < 0.05) while living in urban areas and counties and having a sense of social support were protective factors (P < 0.05). Quarantining due to the pandemic and exercise were independent risk factors for anxiety in FSWs (P < 0.05) while living in counties and having a sense of social support were protective factors (P < 0.05). Quarantining due to the pandemic was an independent risk factor for somnipathy in FSWs (P < 0.05) while being married was a protective factor (P < 0.05). NE/NA was a protective factor for sleep disorders (OR=0.042, P=0.05), with an AUC of 0.87. Conclusion FSWs should appropriately adjust their work form during the pandemic period, maintain a positive and optimistic attitude, establish long-term stable social relationships, and seek a greater sense of social support. The government should provide comprehensive bio-psycho-social interventions to address the mental and physical health status of this population.